2004
DOI: 10.1038/sj.onc.1207322
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine stimulation by osteopontin plays a pivotal role in the expression of the mitogenic and invasive phenotype of RET/PTC-transformed thyroid cells

Abstract: Papillary thyroid carcinomas are characterized by rearrangements of the RET receptor tyrosine kinase generating RET/PTC oncogenes. Here we show that osteopontin (OPN), a secreted glycoprotein, is a major RET/PTC-induced transcriptional target in PC Cl 3 thyroid follicular cells. OPN upregulation depended on the integrity of the RET/PTC kinase and tyrosines Y1015 and Y1062, two major RET/PTC autophosphorylation sites. RET/PTC also induced a strong overexpression of CD44, a cell surface signalling receptor for O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 37 publications
1
34
0
Order By: Relevance
“…Thyroid carcinoma overexpresses CD44 and such overexpression is associated to the oncogenic conversion of the ERK signaling pathway (18,19). Moreover, as in other cell types (42), CD44 was expressed in prospectively identified thyroid cancer stem cells that induce tumors when injected orthotopically into mouse thyroid (43).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Thyroid carcinoma overexpresses CD44 and such overexpression is associated to the oncogenic conversion of the ERK signaling pathway (18,19). Moreover, as in other cell types (42), CD44 was expressed in prospectively identified thyroid cancer stem cells that induce tumors when injected orthotopically into mouse thyroid (43).…”
Section: Discussionmentioning
confidence: 86%
“…CD44 is overexpressed in PTC and in cell lines harboring RET/PTC or BRAF oncogenes (18,19). Here, we show that CD44-ICD triggers activation of the CREB transcription factor; in thyroid cancer cells, RET/PTC-BRAF signaling cascade uses such a CD44-ICD-CREB axis to sustain cell proliferation.…”
Section: Introductionmentioning
confidence: 87%
“…The expression of SPP1͞CD44 has been shown to be triggered by RET͞PTC oncogenes in rat thyroid cells and to sustain tumor cell proliferation and invasion (37).…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19] OPN enhances tumoral cell proliferation increasing the malignant phenotype 16,17,25,26 and its downregulation in cancer cells reduces their growth and tumorigenicity in mice. 27 In line with these observations we found that OPN enhances HMCLs proliferation and increases IL-6 proproliferative effect on myeloma cells.…”
Section: Discussionmentioning
confidence: 99%